Tear Film Evaluation in Contact Lens Wearers and Non Wearers - Shrestha, GS; Sujakhu, D; Shrestha, JB; Shrestha, JK (Journal of Institute of Medicine Nepal, 2013)
Background: Dry eye symptoms are more frequent in contact lens wearers than in non wearers. Dry eye is considered relatively common in contact lens wearers than non-wearers. However, there was no any report in our clinical setting that compared and addressed the issue related to dry eye and its symptom in contact lens wearers. The present study was conducted to compare pre-ocular tear lm in contact lens wearers (CLW) and contact lens non wearers (CLNW), and evaluate the relationship between clinical and subjective assessment of dry eye symptoms. Methods: It was a comparative study conducted among 131 subjects (262 eyes) attended in the contact lens clinic at BP Koirala Lions Center for the Ophthalmic Studies. Sixty five were daily soft contact lens wearers; sixty-six were non wearers. Tear function assessment included non- invasive tear break up time, invasive tear break up time, tear prism height and Schirmer II test. Subjective assessment of dry eye symptoms was carried out using McMonnies questionnaires. Results: Mean age of CLNW was 23.01± 5.53 and CLW was 23.6± 4.61. Female (89 subjects) visited more than male (42 subjects) in contact lens clinic. Mean symptom score in CLW was significantly higher than CLNW (p<0.001). But, distribution of symptomatology was not significantly different in both groups. Symptomatic subjects were elder (p<0.001) and female (p<0.05) in CLNW and only elder subjects in CLW. Tear function tests were significantly lower in symptomatic subjects in CLW and CLNW; Overall tear function test scores were also lower in CLW than CLNW. Tear function tests scores were insignificantly different in male and female. Coefficient of correlation was positive and weak for all tear function tests scores. Conclusions: Though, tear function tests scores were reduced in CLW than CLNW, dry eye symptomatology was almost similar. Subjective assessment of symptoms is as important as clinical tests. DOI: http://dx.doi.org/10.3126/joim.v34i2.9044 Journal of Institute of Medicine August, 2012; 34:2 14-20